Vestibular patients generate more regular head movements than healthy individuals during gaze-stabilization exercises - Cecelia Shuai; Omid A. Zobeiri; Jennifer L. Millar; Michael C. Schubert; Mark Shelhamer; Kathleen E. Cullen (Scientific Reports)
Abstract The vestibular system is vital for maintaining stable vision during daily activities. When peripheral vestibular input is lost, patients initially experience impaired gaze stability due to reduced effectiveness of the vestibular-ocular-reflex pathway. To aid rehabilitation, patients are often prescribed gaze-stabilization exercises during which they make self-initiated active head movements. Analyzing statistical pattern of sequences of stereotyped behaviors to characterize degrees of randomness or repeatability has proven to be a powerful approach for diagnosing disease states, yet this approach has not been applied to patients with vestibular loss. Accordingly, here we investigated whether the patterning of head movements is altered in vestibular-loss patients by using trial-based analysis and sample-entropy measurement. The subjects completed gaze-stability exercises in both the yaw and pitch directions. In trial-based analysis, we calculated the trial-to-trial variability of head movement duration and peak velocity for each individual head movement. Our results showed that healthy individuals exhibited a temporally repetitive (correlated) structure in peak velocity, especially for head movements in the pitch direction, which was absent in most patients. In the sample entropy analysis, which measures the irregularity or randomness of a time series, our results revealed that head-movement generation was more regular in vestibular-loss patients compared to healthy controls. Together, these analyses suggest that vestibular-loss patients display less flexibility in the patterning of their head motions. Our results provide the first experimental evidence that temporal head stability is a valuable metric for distinguishing individuals with impaired vestibular function from healthy ones.